2002
DOI: 10.1258/0022215021911257
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of adult vocal fold length

Abstract: Laryngeal photographs from 165 Taiwanese subjects were taken during microlaryngoscopy. Photographs of the vocal fold during the open phase were chosen. For measuring the vocal fold length, both the photograph of a ruler and the larynx were taken under the operating microscope, thus forming a 'new scale'. Photographs of the vocal fold and the ruler were then processed at the same power of magnification. The length of the vocal folds was measured with the 'new scale'. In 100 patients receiving direct laryngoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 4 publications
2
26
0
1
Order By: Relevance
“…The morphometric dimensions of larynx were described in adults by several researchers [3][4][5][6][7][8][9]. In fetuses, the inadequate literatures regarding this subject were presented [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphometric dimensions of larynx were described in adults by several researchers [3][4][5][6][7][8][9]. In fetuses, the inadequate literatures regarding this subject were presented [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were obtained from each larynx as follows (Figs. [1][2][3][4][5] to allow the relatively slight changes following preservation in formalin.…”
Section: Methodsmentioning
confidence: 99%
“…This same group of researchers previously established a direct relationship between the dimensions of the vocal folds (length, width, and mass) and voice classification (Roers, et al, 2009). It is known that males have longer vocal folds than females (Nishizawa et al, 1988;Hertegård et al, 1993;Su et al, 2002;Schuster et al, 2005;Larsson & Hertegård, 2008;Mürbe, et al, 2011). However, there are also differences in vocal fold length between voice types e.g.…”
Section: Relationship Between Voice Type and Anatomical Featuresmentioning
confidence: 92%
“…Despite differences in measurement techniques and reference points, all authors found that vocal fold dimensions differ not only between genders, with longer folds in adult males, but also between voice categories, with longer vocal folds in basses compared to tenors, and altos compared to sopranos (Pfau, 1973;Nishizawa, et al, 1988;Hertegård, et al, 1993;Eckel, et al, 1994;Benninghoff & Drenckhahn, 2002;Su, et al, 2002;Roers, 2005;Schuster, et al, 2005;Roers, et al, 2007;Larsson & Hertegård, 2008;Shewell, 2009). In general, vocal fold length in males is between 15 and 20 mm and in females between 9 and 13 mm.…”
Section: Adult Males Adult Femalesmentioning
confidence: 99%
“…10 The results obtained from cadavers did not reflect the physiological vocal fold length in a living person. 11 Measurement is extremely difficult after dissection because of the elasticity of the vocal fold. 12 As for the radiography, the vague landmarks in the film make it difficult to measure the vocal fold length precisely.…”
Section: Introductionmentioning
confidence: 99%